Preeclampsia in pregnancy from the perspective of women in the Northwest region of the State of Rio Grande do Sul, Brazil - Claudete Brondani Machado, Neiva; Welter, Ilca; Peripolli Rodrigues, Andressa; Teresinha Krampe Machado, Marieli; Maria de Mello Cardoso, Sandra; Sonaglio Rocha, Lucimara; Agathe Seiffert, Margot (O Mundo da Saúde, 2020)
Preeclampsia represents one of the main causes of maternal death in the world. The objective was to identify the women’s knowledge about preeclampsia in pregnancy. This was a qualitative, exploratory, and descriptive study with 26 women linked to the Pastoral da Criança care service. In order to collect the data, a conversation circle was held in 2014 to discuss and apply a questionnaire with open and closed questions, the data being analyzed by thematic content analysis. The predominance of women of childbearing age who have already experienced motherhood was identified and, therefore, the possibility of complications during pregnancy was exposed. One of the respondents had the disease during pregnancy, seven had some knowledge about the subject, and 19 of them were unaware of the disease. Prenatal care is identified as a way of clarifying the disease and its risk factors. It is necessary to train prenatal and multiprofessional caregivers in assisting women, including health education actions that contribute to improving women’s knowledge about the diseases that permeate the gestational period.